THE INFLUENCE OF BRAND PLACEMENT PRODUCT HAND BODY SCARLETT WHITENING IN KOREA TODAY'S WEBTOON ON BRAND AWARENESS AND PURCHASE INTENTION PRODUCT HAND BODY SCARLETT WHITENING - Balqis Aurora Ariani; Nurainun; Muchsin; M. Subhan (RADJA PUBLIKA, 2024)
This study aims to identify the influence of brand placement (independent) consisting of visual placement, auditory placement, and plot connection on the intention to buy Scarlett brand hand body lotion products. In addition, this study also identified brand awareness (mediation) variables consisting of brand recognition and brand recall as variables that mediate the relationship between brand placement and purchase intention (dependent). The design used in this study is a quantitative design using an online data collection method using a google form. However, before filling out the questionnaire, respondents will be directed to watch snippets of Korean dramas contained in the google form. Sampling was carried out in a convinience & purposive manner. The number of samples used was 120 respondents. Data analysis using PLS-SEM with the WARP PLS application version 7.0. From the results of the study that tested the influence of brand placement on purchase intention with brand reconation and brand recall as mediation variables, it can be concluded that even though the medasi variable is used, only a few variables have an effect when the mediation variable is used, these variables are visual placement and plot connection.